2016
DOI: 10.1002/phar.1849
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Administration Is Associated with Adverse Outcomes in Critically Ill Patients Receiving Parenteral Nutrition: Results from a Natural Experiment Created by a Calcium Gluconate Shortage

Abstract: Calcium administration correlated with adverse outcomes in critically ill patients receiving PN. The data suggest that administration of parenteral calcium to critically ill patients may be harmful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…However, a systematic review of adult literature found no evidence to support treating hypocalcemia of critical illness [350]. Calcium supplementation may actually worsen organ dysfunction and is correlated with adverse outcomes in critically ill adult patients receiving PN [351]. Although the prevalence of hypocalcemia in critically ill children has been reported to be up to 75% and is associated with organ dysfunction [352], no studies in children with septic shock have investigated the effect of calcium supplementation to treat hypocalcemia.…”
mentioning
confidence: 99%
“…However, a systematic review of adult literature found no evidence to support treating hypocalcemia of critical illness [350]. Calcium supplementation may actually worsen organ dysfunction and is correlated with adverse outcomes in critically ill adult patients receiving PN [351]. Although the prevalence of hypocalcemia in critically ill children has been reported to be up to 75% and is associated with organ dysfunction [352], no studies in children with septic shock have investigated the effect of calcium supplementation to treat hypocalcemia.…”
mentioning
confidence: 99%
“…Parenteral Ca administration to critically ill patients has been reported to more than double the mortality risk and the risk of acute respiratory failure (12) . These observations are in line with animal studies and may be related to pro-inflammatory actions by Ca (29) .…”
Section: Discussionmentioning
confidence: 99%
“…However, metaanalyses of both interventional and observational studies have failed to demonstrate this association (10,11) . To our knowledge, the relationship between Ca supplements and respiratory mortality has not been investigated in adults, although parenteral Ca administration to critically ill patients has been associated with an increased risk of acute respiratory failure (12) . In line with supplementation, evidence on the association between milk consumption with disease risk and mortality has produced conflicting results.…”
mentioning
confidence: 99%
“…Therefore, the intersection of the mortality curves was calculated, and we found that patients with calcium supplementation tended to have a higher hospital mortality when their iCa on first ICU admission was approximately 0.94 ~ 1.16 mmol/L, suggesting that attempted blood calcium correction at this interval would be harmful. Because the majority of septic patients' iCa on the first ICU admission was located at this iCa interval, this may explain why some studies revealed that calcium supplementation has an adverse effect on the prognosis of septic patients [16,20] and septic model [21,22]. However, on the contrary, there is a trend showing that calcium supplementation decreased mortality when iCa on the first ICU admission was lower than 0.9 mmol/L and higher than 1.20 mmol/L, although we would not confirm this finding in the survival analysis, probably due to the small number of patients in those subgroups.…”
Section: Calcium Supplementation Had a Double Effect On The Mortalitymentioning
confidence: 99%
“…One large retrospective study showed that calcium supplementation can improve the 28-day and 90-day survival in ICU patients [14]. However, several clinical observation studies have shown that calcium supplementation in critically ill patients provides no benefit or even worsen outcomes [15,16]; moreover, experiments using an animal model of sepsis showed that calcium administration increases mortality [17].…”
Section: Introductionmentioning
confidence: 99%